2020
DOI: 10.1002/ajpa.24116
|View full text |Cite
|
Sign up to set email alerts
|

Sahelian pastoralism from the perspective of variants associated with lactase persistence

Abstract: Objectives: Archeological evidence shows that first nomadic pastoralists came to the African Sahel from northeastern Sahara, where milking is reported by 7.5 ka. A second wave of pastoralists arrived with the expansion of Arabic tribes in 7th-14th century CE. All Sahelian pastoralists depend on milk production but genetic diversity underlying their lactase persistence (LP) is poorly understood. Materials and methods: We investigated SNP variants associated with LP in 1,241 individuals from 29 mostly pastoralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 88 publications
0
22
1
Order By: Relevance
“…This finding seems to be consistent with the difference between the mobility of these lifestyle groups, and therefore also with the limited gene flow between them . This result contrasts with the findings of previous studies on Sahelian populations that analyzed uniparental genetic systems (Černý et al, 2011;Novác ˇková et al, 2020), markers associated with lactase persistence (Priehodová et al, 2020;Vicente et al, 2019), and NAT2 sequences (Podgorná et al, 2015), all of which indicated a relatively high correspondence between subsistence mode and genetic and even phenotypic (Kleisner et al, 2019) structure of populations across the African Sahel/Savannah belt. The present study supports the notion that genetic differentiation between populations at TAS2R16 does not correspond to specific foodproduction strategies; instead it suggests that TAS2R16 variation reflects a geographic structure that was mainly shaped by neutral, demographic processes (Campbell et al, 2014b;Kim et al, 2005;Soranzo et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding seems to be consistent with the difference between the mobility of these lifestyle groups, and therefore also with the limited gene flow between them . This result contrasts with the findings of previous studies on Sahelian populations that analyzed uniparental genetic systems (Černý et al, 2011;Novác ˇková et al, 2020), markers associated with lactase persistence (Priehodová et al, 2020;Vicente et al, 2019), and NAT2 sequences (Podgorná et al, 2015), all of which indicated a relatively high correspondence between subsistence mode and genetic and even phenotypic (Kleisner et al, 2019) structure of populations across the African Sahel/Savannah belt. The present study supports the notion that genetic differentiation between populations at TAS2R16 does not correspond to specific foodproduction strategies; instead it suggests that TAS2R16 variation reflects a geographic structure that was mainly shaped by neutral, demographic processes (Campbell et al, 2014b;Kim et al, 2005;Soranzo et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…The first event is genetically dated to ~1828 years ago and the second one to ~302 years ago, whereby it seems that the admixture involved a group related to southwestern Europeans. Moreover, the geographical distribution of lactase persistence variants in the Sahel/Savannah belt shows clear differences between the pastoralists in the east (mostly Arabs harboring variant −13,915 × G) and the west (mostly Fulani harboring variant −13,910 × T) [ 25 ]. In fact, a boundary between the western and eastern Sahelian genetic spaces lies somewhere near the Lake Chad Basin, as attested not only by lactase persistence but also by a genome-wide SNP study [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like other West African countries such as Nigeria (Chiamogu and Chiamogu 2020), Cameroon (Awazi and Avana-Tientcheu 2020) and Mali (Priehodová et al 2020), Ghana has for some time now been plagued with farmer-herder conflicts (Agyemang 2017;Tonah 2006;Otu, Impraim, and Twumhene 2020) with profound consequences for the country. Not much has been done about the human security costs of these destructive conflicts, creating a scholarly gap in Ghana and the need for an empirical study of this nature.…”
Section: Herders Farmers and Jihadistsmentioning
confidence: 99%